Heart and diabetes consensus: Physical exercise in diabetic patients with cardiovascular diseases. - Eduardo Rivas-Estany; José D. Barrera Sarduy; Rolando Rogés Machado; Maricela Nuez Vilar; Juan A. Álvarez Gómez; Francisco Fernández Valdés (ECIMED, 2011)
Cardiovascular diseases are the leading cause of death in the world, some are preventable through the control of risk factors, but the prevalence of obesityand diabetes are increasing in many countries. The current behavior for the control of diabetes includes nutritional and drug treatment, systematic physicalexercises and patient education. Physical exercise has proven to be beneficial for diabetic patients, particularly for type 2, suffering for ischemic heartdisease with high frequency, because it can provide favorable metabolic and endocrine responses. The reduction of the insulin-resistance is one of themost important effects of the exercises by its direct effect on the metabolism of glucose, insulin and own muscle metabolism. It should therefore be includedin the ideal strategy for treatment of diabetic people to prevent and reduce hyperglycemia in acute and chronic form, avoiding their long-termcomplications. Exercise in diabetics with heart disease should be carried out individually and with special care, after proper ergometric assessment; it hassimilar effects than in non-diabetic individuals.